Histоpathоlоgical Evaluatiоn оf the Neurоprоtective Effects оf Mоringa Leaf Extracts in Methоtrexate-Induced Hippоcampal Damage in Albinо Rats - Mehdar, Khlood M (Trends in Immunotherapy, 2025)
Methotrexate is a widely utilized chemotherapeutic agent known to induce neurotoxic effects, thereby constraining its therapeutic potential across various malignancies. While Moringa leaf extract has demonstrated significant antioxidants and anti-inflammatory properties, its role in mitigating Methotrexate-induced neurotoxicity remains inadequately explored. This study seeks to elucidate the protective effects of Moringa leaf extract on Methotrexate-mediated damage within the dentate gyrus of the hippocampus. Male rats were administered Moringa leaf extract at 300 mg/kg body weight via oral gavage bi-weekly over four weeks. Concurrently, select groups received intraperitoneal injections of 0.5 mg/kg Methotrexate twice weekly for the study. The administration of Methotrexate elicited oxidative stress, as evidenced by elevated levels of malondialdehyde and diminished activity of superoxide dismutase. Histopathological assessments revealed that Methotrexate treatment induced significant alterations in the dentate gyrus, characterized by an inflammatory response marked by the upregulation of Toll-like receptor 4. Activation of the Toll-like receptor 4 signalling pathway consequently led to an increased expression of the Nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3-inflammasome and enhanced caspase-1 activation. Importantly, co-administration of Moringa leaf extract with Methotrexate substantially reduced both inflammatory and oxidative stress markers while restoring the dentate gyrus’s structural integrity. Moringa leaf extract demonstrates potent antioxidant and anti-inflammatory properties that effectively counteract Methotrexate-induced neurotoxicity by modulating the brain’s TLR4/NLRP3/caspase-1 signalling axis.